Therapeutic potential of targeting interleukin‐1 family cytokines in chronic inflammatory skin diseases - Calabrese, Laura; Fiocco, Zeno; Satoh, Takashi K.; Peris, Ketty; French, Lars E. (British journal of dermatology (1951), 2022)
Summary The interleukin (IL)‐1 family of cytokines is a central regulator of a myriad of immunological responses. It comprises several cytokines, including those belonging to the IL‐1, IL‐36 and IL‐18 subfamilies, as well as IL‐33. The IL‐1 family primarily plays a role in orchestrating innate immune responses, but is also involved in adaptive immunity. Increased interest in the IL‐1 family occurred following the discovery that dysregulation of IL‐1 signalling underlies the pathogenesis of several monogenic autoinflammatory diseases, characterized by sterile inflammation involving the skin and other organs. This also provided increased understanding of the role of innate immunity and the IL‐1 family in polygenic autoinflammatory skin conditions, such as neutrophilic dermatoses, as well as in some of the most common chronic inflammatory skin diseases, such as psoriasis and hidradenitis suppurativa. Several therapeutic agents have been developed to inhibit the IL‐1 family members and their signalling pathways. These have shown therapeutic efficacy in several chronic inflammatory skin disorders. The aim of this review is to thoroughly describe the consequences of pathological dysregulation of the IL‐1, IL‐33, IL‐36 and IL‐18 pathways in dermatological conditions and to provide a forward‐looking update on therapeutic strategies targeting signalling by IL‐1 family cytokines. Plain language summary available online